Does gender equality contribute to growth? excerpt from Progresss of the World's Women 2015-2016 : transforming economies, realizing rights. (2015)
Argues that improving substantive equality for women and realizing their human rights require a rethinking of macroeconomics.
Keywords: GENDER EQUALITY